DEVELOPING SPEAKING SKILLS THROUGH INTERACTIVE ACTIVITIES - Zokirova Dildora Baxtiyarovna (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2026)
Abstract: Speaking is an essential skill in learning English as a Foreign Language (EFL) because it enables learners to communicate ideas, opinions, and information effectively. However, many students experience difficulties in speaking due to limited vocabulary, lack of confidence, pronunciation problems, and insufficient practice. This article examines the role of interactive activities in developing speaking skills among EFL learners. Interactive activities such as role plays, group discussions, debates, storytelling, games, and information-gap tasks create meaningful opportunities for communication and increase student participation. The article also discusses the importance of technology-based tools in improving speaking fluency and pronunciation. Furthermore, it highlights the role of teachers in creating supportive and student-centered learning environments. The study concludes that interactive activities significantly improve learners’ fluency, confidence, motivation, pronunciation, and communicative competence, making them an effective approach in modern language teaching.